Secrecy Performance of Untrustworthy AF Relay Networks using Cooperative Jamming and SWIPT - Egashira, E. N. [UNESP]; Benitez Olivo, E. E. [UNESP]; Moya Osorio, D. P.; Alves, H.; IEEE (Ieee, 2019)
In this paper, the secrecy outage performance of a three-node amplify-and-forward relay network with an untrustworthy relay is investigated. To enable a secure transmission, we consider a destination-based jamming technique to prevent the relay from successfully decoding the secret messages between the source and the destination. In addition, the relay is assumed to be an energy-constrained device, thus being first energized by the source in order to be able to retransmit the information to the destination. In doing so, a time switching-based simultaneous wireless information and power transfer scheme is used. A closed-form asymptotic expression for the secrecy outage probability is derived in order to obtain a tight approximation at medium-to-high signal-to-noise ratio. The accuracy of the performed analysis is corroborated by Monte Carlo simulations through different illustrative cases. Numerical results show the impact of key system parameters on the secrecy performance, such as the time allocation factor between the energy harvesting and information transmission phases, the power allocation factor between source and destination for cooperative jamming, and the relay position, so as to provide insights on the design criteria for energy efficient and secure networks.
Keywords: Cooperative jamming; physical layer security; secrecy outage probability; SWIPT; untrustworthy relay